Comment on 'Growth Empirics and Reality,' by William A. Brock and Steven N. Durlauf - Sala-i-Martin, Xavier (Washington, DC: World Bank, 2014)
William Brock and Steven Durlauf's article nicely summarizes some of the recent research on Bayesian model averaging. They make a number of important points. One is that the empirics of growth face three key problems: model uncertainty, parameter uncertainty, and endogeneity. They argue that theory uncertainty can be dealt with using Bayesian model averaging methods.